Inclusive practices in the pedagogical mediation: are we prepared? - Mejías Vindas, Maricruz (2019)
This scientific article is the result of a mixed type of research whose purpose was to carry out a diagnosis on the training needs of teachers of the Regional Office of the West about the issues related to inclusive education. For the collection of data, 36 schools of the different school circuits were considered, as well as authorities of the Regional Office that are directly related to the subject. The instruments used were questionnaires, interviews, focus groups and observation guides. Among the main results found is the difficulty of teachers to implement inclusion in their pedagogical practice due to lack of training and knowledge regarding the subject. Hence, it is urgent to open spaces that allow teachers to train in different methodologies, languages ​​and techniques that allow them to address the diversity of the classroom.